Kinetics of Methane Hydrate Formation in an Aqueous Solution with and without Kinetic Promoter (SDS) by Spray Reactor - Yaqin Tian; Yugui Li; Hongping An; Jie Ren; Jianfeng Su (Journal of Chemistry)
Hydrate formation apparatus reported so far was mainly concentrated in stirred-tank batch environments. It was difficult to produce the high gas storage hydrate efficiently. Some nonstirred technology has been attracting more attention by researchers. This work proposed a new apparatus for hydrate formation by spraying water into a gaseous phase with a fine nozzle. It can get sufficient contact surface area for gas-liquid reaction. Methane hydrate formation experiments have been conducted using pure water and sodium dodecyl sulfate (SDS) aqueous solution for comparison at 277.15 K. The experiments were conducted at 7.0 and 6.0 MPa, respectively. Kinetics of methane hydrate formation have been investigated by methane consumption per mole of water and reaction rate. The mechanism of hydrate formation and kinetics property by spraying atomization were studied with the theory of crystal chemistry.